2022
DOI: 10.3102/01623737221113576
|View full text |Cite
|
Sign up to set email alerts
|

Misunderstanding Law: Undergraduates’ Analysis of Campus Title IX Policies

Abstract: Colleges and universities are legally required to attempt to prevent and redress sexual violations on campus. Neo-institutional theory suggests that the implementation of law by compliance professionals rarely achieves law’s goals. It is critical in claims-based systems that those who are potential claimants understand the law. This article demonstrates that (a) intended subjects of the law (colleges and universities) interpret and frame the law in very similar ways; (b) resultant policies are complex and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This Article highlights the noteworthy works of scholars such as Laura Gomez, Kaaryn Gustafson, Dorothy Roberts, Spencer Headworth, KT Albiston and Michael McCann, who have explored various facets of relationality within legal scholarship. Additionally, I provide insights into my own research, rooted in the concept of a "situated approach," as applied to diverse areas, ranging from offensive public speech (Nielsen 2000) to employment civil rights (Berrey 2017;Berrey et al 2012), the politics of good moms with guns (Nielsen 2019) and the regulation of sexual consent on college campuses (Albrecht et al 2023). My approach integrates interpretivist concerns regarding hegemonic systems of meaning and power with institutionalists' considerations of the contextual impact of law.…”
Section: Blossoms: Relational Rights In the Sociolegal Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…This Article highlights the noteworthy works of scholars such as Laura Gomez, Kaaryn Gustafson, Dorothy Roberts, Spencer Headworth, KT Albiston and Michael McCann, who have explored various facets of relationality within legal scholarship. Additionally, I provide insights into my own research, rooted in the concept of a "situated approach," as applied to diverse areas, ranging from offensive public speech (Nielsen 2000) to employment civil rights (Berrey 2017;Berrey et al 2012), the politics of good moms with guns (Nielsen 2019) and the regulation of sexual consent on college campuses (Albrecht et al 2023). My approach integrates interpretivist concerns regarding hegemonic systems of meaning and power with institutionalists' considerations of the contextual impact of law.…”
Section: Blossoms: Relational Rights In the Sociolegal Fieldmentioning
confidence: 99%
“…In alignment with this work, my own research has long been centered on legal consciousness and the significance of relationality. I have employed what I often refer to as a "situated approach" in various studies, including those on offensive public speech (Nielsen 2000), employment civil rights (Berrey et al 2012) and the regulation of sexual consent on college campuses (Albrecht et al 2023). This approach aligns with interpretivists' concerns regarding hegemonic systems of meaning and power, while also drawing on the institutionalists' perspective of how the law's impact varies across different contexts.…”
Section: Blossoms: Relational Rights In the Sociolegal Fieldmentioning
confidence: 99%
“…Public views of the legal system have long been of interest to scholars. A large literature, for example, has explored gaps between public understanding of substantive legal rules and the rules themselves, identifying areas in which lay knowledge is limited (Albrecht et al, 2022; Darley et al, 2001; Kim, 1998; MacCoun et al, 2009; Rowell, 2019). Related work has shown that people's intuitions about the law are sometimes congruent with—but sometimes depart from—the law itself (Robbennolt & Hans, 2016; Robinson & Darley, 1995).…”
Section: Understanding Settlementmentioning
confidence: 99%
“…These policies change and evolve regularly, often without the consent or knowledge of the general population. Since the policies are so complex and change so often, students struggle to understand them (Albrecht et al, 2022), and there are few—if any—experts on an individual university's sexual misconduct policy outside of organizational actors. I argue that this creates an “organizational dependency,” in which survivors who seek to use the campus policy must rely on university representatives to make sense of their rights and the decisions before them.…”
Section: Literature Reviewmentioning
confidence: 99%